2000
DOI: 10.1054/bjoc.2000.1495
|View full text |Cite
|
Sign up to set email alerts
|

Markers of infection, breast-feeding and childhood acute lymphoblastic leukaemia

Abstract: Summary Infections are suspected to play a role in the aetiology of childhood leukaemia. In 1989-95, we evaluated the relation between childhood acute lymphoblastic leukaemia and pre-and postnatal markers of exposure to infection, as well as breast-feeding. A populationbased case-control study was carried out in certain regions of Québec, Canada, in 1989-95 including 491 incident cases diagnosed between 1980 and 1993 and aged between 0 and 9 years. An identical number of healthy controls matched for age, sex a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
125
2
4

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 31 publications
7
125
2
4
Order By: Relevance
“…Several previous studies on incident cases (Van Steensel-Moll et al, 1986;Petridou et al, 1997;Bener et al, 2001), and, in particular, several mortality studies (Stewart et al, 1958;MacMahon and Newill, 1962;Stark and Mantel, 1966) found that being the firstborn increased the risk of, or mortality related to, childhood AL. We did not find such an association, in line with many other studies based on incident cases (Shaw et al, 1984;McKinney et al, 1987;Kaye et al, 1991;Savitz and Ananth, 1994;Cnattingius et al, 1995;Roman et al, 1996;Shu et al, 1999;Infante-Rivard et al, 2000;Neglia et al, 2000;Rosenbaum et al, 2000). An OR less than unity, but far from significance, was observed with respect to a time interval to birth of the immediately elder sibling of less than 2 years, as was reported by Kaye et al (1991), but not by Neglia et al (2000).…”
Section: Epidemiologysupporting
confidence: 88%
“…Several previous studies on incident cases (Van Steensel-Moll et al, 1986;Petridou et al, 1997;Bener et al, 2001), and, in particular, several mortality studies (Stewart et al, 1958;MacMahon and Newill, 1962;Stark and Mantel, 1966) found that being the firstborn increased the risk of, or mortality related to, childhood AL. We did not find such an association, in line with many other studies based on incident cases (Shaw et al, 1984;McKinney et al, 1987;Kaye et al, 1991;Savitz and Ananth, 1994;Cnattingius et al, 1995;Roman et al, 1996;Shu et al, 1999;Infante-Rivard et al, 2000;Neglia et al, 2000;Rosenbaum et al, 2000). An OR less than unity, but far from significance, was observed with respect to a time interval to birth of the immediately elder sibling of less than 2 years, as was reported by Kaye et al (1991), but not by Neglia et al (2000).…”
Section: Epidemiologysupporting
confidence: 88%
“…Two of these previous studies restricted their analysis to children diagnosed between age 2 and 5 years and found no significant effect of breastfeeding on risk of leukaemia (Shu et al, 1995;UK Childhood Cancer Study Investigators, 2001). In contrast, five case -control studies (Shu et al, 1999;Smulevich et al, 1999;Infante-Rivard et al, 2000;Bener et al, 2001;Perrillat et al, 2002a, b) have reported a statistically significant protective association between breastfeeding and risk of either childhood ALL or overall leukaemia. One of these studies described a borderline statistically significant effect of breastfeeding on risk of ALL among children diagnosed less than 4 years of age (InfanteRivard et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…[23][24][25][26] Interestingly, a number of protective factors have been reported to reduce the risk for these hematologic malignancies. Several epidemiologic studies demonstrate a protective effect of whole-day care of children in the age group 0-4 and of intermittent infections in this time period for leukemias, [27][28][29][30][31][32][33] lymphomas, 34 Hodgkin's disease 35,36 and neuroblastomas. 37 Other studies, unable to confirm this directly, quoted significant effects of other socioeconomic parameters increasing the risk for the respective diseases, such as parameters suggestive of a protected environment in early childhood in the case of leukemias, 38,39 or a higher level of education in Hodgkin's lymphoma.…”
Section: Epidemiologic Datamentioning
confidence: 99%